Investigating Mass Transfer Phenomena in Batch Solvent Extraction of Rice Bran Oil - Lienda Aliwarga (Dept. of Chemical Engineering, Diponegoro University, 2019)
In this study, we will point out the correlation of critical parameters in designing scale-up of process equipment for commercial rice bran oil extraction with different types of rice paddy, solvent, and physicochemical condition. Advantageously, this research was also intended to enhance the discoveries of novel sustainable production method for resilient agro-based food, energy, and chemical industries. In our experiment, the extraction of rice bran oil was organised in a batch agitated vessel and showed a profile of first order system. The most important factors which profoundly contributed towards the yield of rice bran oil from Saigon I and PadiBesar variety are temperature (T), impeller speed (N), ratio of bran to solvent (s/L), and ratio of impeller’s height-off bottom to tank diameter (h/d). For the mass transfer constant and the rate of extraction as consequence, factors that significantly influenced the correlation were temperature (T), impeller speed (N), ratio of impeller diameter to tank diameter (d/D), and ratio of impeller’s height-off bottom to tank diameter (h/d). For the dimensionless yield, generalised equation is provided with coefficient of determination 0.95, while that of the mass transfer equals to 0.63, reflecting the yield correlation to be more accurate in predicting further experimental results. These correlations are furthermore unique for different rice varieties, of which in this case belongs to Saigon I. Application for other rice species is relevant as by inserting additional correction factor which also exemplified in this research for PadiBesar. Keywords: rice bran oil; batch extraction; storage time; mass transfer, rate, yield